Study of Halal Certification for Food Products from a Sharia Law Perspective - Faruq Naufaldi Bintoro; Muthoifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Halal certification and labeling is a form of renewal that occurs in the food and public consumption sector. Halal certification and labeling on food in circulation, especially instant food, is something that actually did not exist in the past, but now its existence is something that is considered important. This paper is a conceptual research related to the study of halal certification and labeling on food in the perspective of Islamic law through the study of ayat ahkam. The results of the study show that halal certification and labeling on food can actually be viewed by returning to the basic rule in terms of food, namely